Fishing impact and environmental status in European seas: a diagnosis from stock assessments and ecosystem indicators. Issue 1 (1st August 2014) - Gascuel, Didier; Coll, Marta; Fox, Clive; Guénette, Sylvie; Guitton, Jérome; Kenny, Andrew; Knittweis, Leyla; Nielsen, J Rasmus; Piet, Gerjan; Raid, Tiit; Travers‐Trolet, Morgane; Shephard, Samuel
Abstract: Stock‐based and ecosystem‐based indicators are used to provide a new diagnosis of the fishing impact and environmental status of European seas. In the seven European marine ecosystems covering the Baltic and the North‐east Atlantic, (i) trends in landings since 1950 were examined; (ii) syntheses of the status and trends in fish stocks were consolidated at the ecosystem level; and (iii) trends in ecosystem indicators based on landings and surveys were analysed. We show that yields began to decrease everywhere (except in the Baltic) from the mid‐1970s, as a result of the over‐exploitation of some major stocks. Fishermen adapted by increasing fishing effort and exploiting a wider part of the ecosystems. This was insufficient to compensate for the decrease in abundance of many stocks, and total landings have halved over the last 30 years. The highest fishing impact took place in the late 1990s, with a clear decrease in stock‐based and ecosystem indicators. In particular, trophic‐based indicators exhibited a continuous decreasing trend in almost all ecosystems. Over the past decade, a decrease in fishing pressure has been observed, the mean fishing mortality rate of assessed stocks being almost halved in all the considered ecosystems, but no clear recovery in the biomass and ecosystem indicators is yet apparent. In addition, the mean recruitment index was shown to decrease by around 50% in all ecosystems (except the Baltic). We conclude that building this kind of diagnosis is a key step on the path to implementing an ecosystem approach to fisheries management.